Hidrocarbonetos Policíclicos Aromáticos (HPAs) em Grãos de Milho Submetidos à Secagem com Queimador de Cavaco - Branco, Telvi Marcelo (2021)
The burning of any organic material can generate chemical compounds called HPA’s, which have carcinogenic and mutagenic potential. This work aimed to detect the existence or not of Polycyclic Aromatic Hydrocarbons (PAHs) in corn kernels (Zea mays L.), after being subjected to artificial drying, where the system used was a grain dryer heated by a burner powered by Wood Chip. To carry out the work, a column dryer with a capacity of 150 t.h⁻¹ and a Eucalyptus wood chip burner (Eucalyptus sp.), with a capacity of 8.6 Gcal were used. The study has a literature review on the main topics involved in the drying process. The main challenge of corn storage is to maintain the physical, chemical and biological properties of the grains. Both the moisture in the air and the moisture in the grains did not interfere with the production of hydrocarbons. The grain drying system with the chip burner had the advantages of automation and reduction in labor, temperature stability and control, air flow modulation, fuel economy, possibility of drying any type of grain, ease of drying of seeds and elimination of fire risks, and the disadvantages, that the chip must remain in a covered place and must have uniform pieces. Initially the cost of the chip is high, however when diluted in the process it becomes advantageous. There are grains that arrive at the unit contaminated, as well as the drying process depending on the conditions may or may not increase these rates, in this study there was the production of Hydrocarbons, even if at rates below international limits, which were used as comparatives.